EVALUATION OF PRE-SYMPTOM ACTIVITY OF FUNGICIDES ON SYMPTOM EXPRESSION, CONIDIA PRODUCTION AND VIABILITY OF VENTURIA INAEQUALIS - G. K. GUPTA, VIJAY THAKUR* AND (Indian Phytopathology, 2002)
All eight ergosterolÂ·biosynthesisÂ·inhibiting (EBI) fungicides (bitertanol, etaconazole, myclobutanil, penconazole + captaf, Hexaconzole (pp 523), prochloraz, fenarimol and triforine) shared with carbendazim, thiophanate-methyl, dodine and guazatine, a high level of presymptom activity whereby lesions developed on the leaves were atypical and either chlorotic or reddish brown flecks. Such atypical lesions had reduced viable sporulation.